Introduction to Virtual Lab Polymerase Chain Reaction (PCR) Practicals in Biology Education at UIN Jakarta - Solihin Solihin; Septiandita Mailayfaiza; Ria Ria; Najwa Syafkitamsana; Lia Junita Harahap; Putri Giriyanti (UIN Syekh Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Polymerase Chain Reaction (PCR) is a fundamental biotechnology technique used to amplify specific DNA fragments in large quantities through in vitro replication. This virtual laboratory aims to (1) understand the basic principles and working stages of PCR, (2) identify the main functions of PCR components, and (3) apply PCR simulations to amplify target genes using the LabXchange platform. The research was conducted virtually, using an interactive experimental approach, by 60 Biology Education students working in one group. Data were collected from student worksheets and simulation outputs. The results showed that students were able to identify and explain each stage of the PCR process, including denaturation, annealing, and extension, as well as analyze the roles of the DNA template, primers, dNTPs, buffer, and Taq polymeraseenzyme. The simulation successfully demonstrated efficient amplification of the target gene. These findings indicate that virtual laboratory learning effectively enhances students’ conceptual understanding and analytical skills in biotechnology.